High flux and high selectivity carbon nanotube composite membranes for natural organic matter removal - Lee, Jieun; Ye, Yun; Ward, Antony J.; Zhou, Cuifeng; Chen, Vicki; Minett, Andrew I.; Lee, Sanghyup; Liu, Zongwen; Chae, So-Ryong; Shi, Jeffrey (ELSEVIER SCIENCE BV, 2016)
Multi-wall carbon nanotubes (MWCNTs)/polyaniline (PANI)/polyethersulfone (PES) membranes were fabricated by incorporation of in-situ polymerised MWCNTs/PANI complex for effective removal of natural organic matter (NOM) in water. The membrane showed high permeability (1400 L/m(2)/h (LMH)/bar), which is 30 times greater than the PES membrane. High NOM rejection rate (80%) was also observed for the composite membrane, which is 4 times higher than PES membrane. This superior performance is attributed to the synergetic effect of increased porosity, narrow pore size distribution and hydrophilicity, and positively charged of the membranes by the inclusion of MWCNT5/PANI complex. MWCNT5/PANI electron transfer complex successfully engineered chemical/physical properties of the membrane in order to have high NOM adsorption capacity and fast water flux. It is suggested that enhanced adsorption capacity is attributed to the electrostatic interaction between NOM and the membrane surface. Key factors contributing to the fast water flux and removal mechanism were covered in depth by characterization of physical and chemical properties of the membrane. The membrane demonstrated 100% water flux recovery and 65% total fouling ratio after cleaning with 0.1 M HCl/0.1 M NaOH solution for 1 h. (C) 2016 Elsevier B.V. All rights reserved.